Sphingosine-1-phosphate induces islet β-cell proliferation and decreases cell apoptosis in high-fat diet/streptozotocin diabetic mice - He, Yizhi (Exp Ther Med, 2019)
Sphingosine-1-phosphate (S1P) has been reported to enhance the function of islet β-cells, providing a potential therapeutic target for diabetes mellitus. In the present study, the effects of S1P on the proliferation and apoptosis of β-cells in type 2 diabetic mice were investigated. The mice were administered intraperitoneal S1P solution daily at a dose of 20 µg/kg for three weeks. The intraperitoneal glucose tolerance test (IPGTT) and homeostatic model assessment of insulin resistance (HOMA-IR) index determination were carried out. Immunohistochemical staining was used to detect the protein expression of insulin, antigen Ki-67 and S1P receptor isoforms (S1PR1/S1PR2/S1PR3) in pancreatic islets. Compared with the diabetic control (DC) group, the IPGTT results and HOMA-IR index in the S1P treatment group were decreased. The islets in the S1P group exhibited higher insulin immunostaining intensity than the DC group, as well as higher proliferation (P<0.05) and lower apoptosis rates (P<0.05). Positive staining for the S1P receptors S1PR1, S1PR2 and S1PR3 was observed in the cytoplasm and membrane of the islet cells. S1PR1 and S1PR2 proteins showed increased expression in the S1P and DC groups compared with the normal control group (P<0.01 and P<0.05, respectively), whereas no significant difference was observed in the expression of S1PR3 among these groups. In conclusion, extracellular S1P can induce islet β-cell proliferation and decrease cell apoptosis in diabetic mice. S1P function may be mediated via S1PR1 and S1PR2; therefore, targeting S1P/S1PR signalling pathways may be a novel therapeutic strategy for diabetes mellitus.